Asymptotic solution of the high order partial differential equation - Da, Hoang Van; Son, Tran Dinh; Tinh, Nguyen Duc (Vietnam Journal of Mechanics, 2009)
In the present paper, the authors have constructed an asymptotic solution of the high order equation with partial derivatives by means of the asymptotic method for the high order systems. The improved first approximation of the solution of the given boundary value problem is determined